Can titanium miniplates provide superior fixation compared to reconstruction plates in mandibular repair with iliac crest flaps? A retrospective study - Lin, Wen-qing; Liu, Da; Zhou, Renbin; Lin, Hao; Zeng, Bang; Jia, Jun; Zhao, Yifang; Liu, Bing; Wu, Tianfu (Frontiers in Bioengineering and Biotechnology, 2025)
This study retrospectively analyzed 112 patients who underwent mandibular reconstruction with vascularized iliac crest flaps using different fixation strategies in routine clinical practice. Under comparable defect lengths and heights, reconstruction using mini plates was associated with the shortest operative time (p < 0.001), while postoperative drainage duration showed no significant difference among groups (p = 0.958). The number of iliac bone segments varied significantly among fixation methods: reconstruction plates (alone or combined with mini plates) were predominantly applied in multi-segmental reconstructions, whereas mini plates were mainly used for single-segmental repairs. Postoperative quality of life was evaluated using the University of Washington Quality of Life Questionnaire (UW-QoL). Although the fixation methods were selected according to defect complexity and surgical requirements, all approaches achieved satisfactory outcomes, and no significant difference in overall quality-of-life scores was observed among the three groups (p = 0.354). However, a significant difference was observed in the “Swallowing” domain, with patients in the mini plate group reporting better swallowing function (p = 0.009).